Segmental Phenolization for the Treatment of in Growing Toenails - Hussain Alwan Al_Obaidy (Diyala Journal of Medicine, 2019)
Background: Ingrown toe nail is a common condition which causes lot of discomfort and morbidity. Though ingrown toenail recognized since long, a satisfactory treatment remains elusive. The range of treatment is from conservative management to amputation of distal part of big toe, but the quest for the ideal procedure remains. Many of the procedures used for treating this painful condition cause considerable discomfort and have high failure rates.